2019
DOI: 10.1016/j.est.2019.100954
|View full text |Cite
|
Sign up to set email alerts
|

Innovative composite sorbent for thermal energy storage based on a SrBr2·6H2O filled silicone composite foam

Abstract: This paper reports about the first experimental activity on a composite material for thermal energy storage, based on a SrBr2ꞏ6H2O filled silicone foam. The morphological and thermal features of the composite with different salt content (i.e. between 40 wt.% and 70 wt.%) were investigated. The dehydration behaviour was studied by thermo-gravimetric analysis. Furthermore, scanning electron and 3D optical microscopy were used to compare the cellular microstructure of the composite foams.The synthesized foams are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 39 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…In previous studies on SAPOs and AlPOs [160][161][162][163], the water adsorption mechanism was revealed, especially for structural phase-dependent water diffusivity at various concentrations and Si/Al ratios, by means of molecular dynamics (MD), density functional theory (DFT) computations [162], nuclear magnetic resonance (NMR) [160], and X-ray diffraction (XRD) [160,163]. AlPOs and SAPOs can load larger amounts of water than silica gel, showing a superior ability to bind to water [164]. Both of them process a higher energy storage capacity of 200-240 Wh/kg at a moderate desorption temperature of 75 to 140 • C [165].…”
Section: Silica Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on SAPOs and AlPOs [160][161][162][163], the water adsorption mechanism was revealed, especially for structural phase-dependent water diffusivity at various concentrations and Si/Al ratios, by means of molecular dynamics (MD), density functional theory (DFT) computations [162], nuclear magnetic resonance (NMR) [160], and X-ray diffraction (XRD) [160,163]. AlPOs and SAPOs can load larger amounts of water than silica gel, showing a superior ability to bind to water [164]. Both of them process a higher energy storage capacity of 200-240 Wh/kg at a moderate desorption temperature of 75 to 140 • C [165].…”
Section: Silica Gelmentioning
confidence: 99%
“…Microporous or macroporous silicon foams are well interconnected, creating a continuity network and effective vapor permeability to allow for vapor flow into or out of pores for both low and high salt contents during the adsorption and desorption phases [164]. Good elasticity and flexibility of this foam can improve the mechanical stability and cyclicity, especially for salt hydrate volume expansion during the adsorption process [164,183,184]. Adsorption capacity of various host matrices at specified conditions [60,110,124,134,150,151,170,181,182].…”
Section: Peer Review 21 Of 58mentioning
confidence: 99%
“…(2009b), the authors also experienced that magnesium sulfate is unable to uptake water above 50 °C unless very high relative humidity is applied (~80% R.H). Magnesium sulfate has also been widely studied in composite salt in the matrix with numerous matrices to solve the agglomeration and stability issues (Whiting et al, 2014;Casey et al, 2014;Hongois et al, 2014;Posern et al, 2015;Xu et al, 2017;Sutton et al, 2018a;Xu et al, 2018;Wang et al, 2019a;Calabrese et al, 2019;Mahon et al, 2019;Miao et al, 2021).…”
Section: Magnesium Sulfatementioning
confidence: 99%
“…Also, hydrothermally stable metal−organic frameworks (MOFs), 27 aerogels, 24 carbon based materials, 5 and porous glass 28 were tested as matrices and different salts like SrBr 2 , copper, potassium, and sodium salt hydrates were explored as impregnates 24,29,30 to improve the CSPM storage materials. Additionally, synthesized matrices such as polymers 31,32 and silicone foams 33,34 were tested. Thereby, it was found that CSPM has generally better sorption kinetics than pure salt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Also, hydrothermally stable metal–organic frameworks (MOFs), aerogels, carbon based materials, and porous glass were tested as matrices and different salts like SrBr 2 , copper, potassium, and sodium salt hydrates were explored as impregnates ,, to improve the CSPM storage materials. Additionally, synthesized matrices such as polymers , and silicone foams , were tested. Thereby, it was found that CSPM has generally better sorption kinetics than pure salt. ,, It was also determined that a higher salt content in the composite results in higher water uptake and energy densities. , However, a too-high salt content could block pores off, mainly in microporous materials …”
Section: Introductionmentioning
confidence: 99%